2013
DOI: 10.1371/annotation/99ad70ea-d3ca-485c-a1b4-50c107941c94
|View full text |Cite
|
Sign up to set email alerts
|

Correction: The Stimulatory Adenosine Receptor ADORA2B Regulates Serotonin (5-HT) Synthesis and Release in Oxygen-Depleted EC Cells in Inflammatory Bowel Disease

Abstract: Objective:We recently demonstrated that hypoxia, a key feature of IBD, increases enterochromaffin (EC) cell 5-HT secretion, which is also physiologically regulated by the ADORA2B mechanoreceptor. Since hypoxia is associated with increased extracellular adenosine, we wanted to examine whether this nucleotide amplifies HIF-1a-mediated 5-HT secretion. Design:The effects of hypoxia were studied on IBD mucosa, isolated IBD-EC cells, isolated normal EC cells and the EC cell tumor derived cell line KRJ-1. Hypoxia (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In addition, HIF1A induces regulatory phenotypes in T-cells [91,92] and significantly induces IL-10 expression in Th17 cells [89], affecting genes in metabolic, anti-apoptotic, cell cycle and T-cell functional pathways. Interestingly, adenosine receptor engagement increases hypoxic signalling while HIF1A upregulates adenosine receptors [93][94][95][96], thereby closely linking hypoxic and adenosinergic signalling. Thus, our data suggest that hypoxic signalling may act as a link between adenosine receptor stimulation and generation of noninflammatory Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HIF1A induces regulatory phenotypes in T-cells [91,92] and significantly induces IL-10 expression in Th17 cells [89], affecting genes in metabolic, anti-apoptotic, cell cycle and T-cell functional pathways. Interestingly, adenosine receptor engagement increases hypoxic signalling while HIF1A upregulates adenosine receptors [93][94][95][96], thereby closely linking hypoxic and adenosinergic signalling. Thus, our data suggest that hypoxic signalling may act as a link between adenosine receptor stimulation and generation of noninflammatory Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine may also hamper immune response mediated by T cell and reduce inflammation which might suggest rationale for predisposition to observed bacteriemia in RDV users (Galan et al, 2009; Layland et al, 2014; Lucijanic et al, 2022, 2023; Vijayan et al, 2017). It has been shown that a hypoxemic setting in inflammatory bowel disease stimulates serotonin synthesis and release and is potentiated by adenosine agonist (Dammen et al, 2013). Although a connection between SSRI and RDV pharmacodynamics remains elusive and current mechanisms unknown, our study suggests that these two drug classes might have a higher incidence of adverse events when used together.…”
Section: Discussionmentioning
confidence: 99%
“…The adenosine A 2B receptor–HIF signaling pathway is one intracellular pathway that would likely not be activated by A 2B receptor agonists administered in normoxic culture, due to the requirement for hypoxia to cause inactivation of the HIF-regulating prolyl hydroxylase (PHD) enzymes and subsequent stabilization of HIF-α proteins [7,49]. Adenosine and the A 2B receptor amplify HIF signaling under hypoxic conditions, contributing to further stabilisation of HIF protein and activation of HIF-mediated transcription in neuroendocrine enterochromaffin cells of the gut [50], smooth muscle cells [32], oral squamous cell carcinoma cells [51], cardiomyocytes [33] and microglial cells [52], as well as in adenosine deaminase-deficient mice and in vivo models of sickle cell disease [32]. Activation of this signaling pathway leads to an A 2B receptor- and HIF-dependent increase in glycolytic metabolism [33,52].…”
Section: Discussionmentioning
confidence: 99%